Mediation Starring role of Student’s Satisfaction in Open Distance Learning in Sri Lanka - Perera, M. J. Renuka; Abeysekera, Nalin (Archives of Business Research, 2019)
In the education environment Students’ Perceived Service Quality (SQ), Satisfaction (SAT) and students’ favourable or unfavourable behaviour can be considered as significant factors of students’ retention and accomplishment of registered programmes with in their stipulated time. The Open Distance Learning (ODL) is widely spread and established flexible pedagogy system with the fast-growing technological enhancement. Year by Year the student population has been drastically increased but completion rate has uncovered a very challenging situation. The service quality concepts which were limited only for customer-based criteria have originated various service quality significant factors and models in education field also. The purpose of this paper is to find out the significant service quality factors by using the modified SERVQUAL dimensions and the relationship between PSQ, SAT and Behavioural Intention (BI). For this study independent variables are Assurance, Empathy, Reliability, Responsiveness, and Website Content and dependent variables are Students’ PSQ, SAT and BI. The population was undergraduate students who have registered for academic year 2013/2014. The valid sample consisted with 744 students. Data collection were done by using a self-administered questionnaire and survey method. The significant relationships revealed; PSQ with Reliability, Responsiveness and Website Content. Further Students’ PSQ with SAT, PSQ with BI and SAT with BI. It is concluded that there is a strong relationship between PSQ and SAT in the ODL environment and a mediated relationship. The variance extracted from the PSQ and SAT were 26% and BI was 43%. It is recommended to select more SQ variables and should increase the sample size for more accuracy in future study as longitudinal. The implications will contribute theoretically and managerially to formulate practical guidelines and necessary strategies to improve the students’ favorable behaviour mediated by the Students’ SAT and PSQ.